2006
DOI: 10.1093/carcin/bgl103
|View full text |Cite
|
Sign up to set email alerts
|

Radiation clastogenesis and cell cycle checkpoint function as functional markers of breast cancer risk

Abstract: Constitutive radiation hypersensitivity in blood lymphocytes and lymphoblasts was not a useful biomarker for identifying women at increased risk of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 51 publications
1
17
1
Order By: Relevance
“…Two hundred microliters of blood was eluted in a final volume of 200 µl that, according to the manufacturer, yields 15-60 ng/µl of DNA. DNA from UNC breast cancer patient samples were obtained from lymphoblastoid cell lines as described previously (39). Paraffin-embedded tissue (PET) samples from breast cancer patients were used for DNA isolation in the event there was insufficient DNA isolated from the blood samples.…”
Section: Genotype Analysismentioning
confidence: 99%
“…Two hundred microliters of blood was eluted in a final volume of 200 µl that, according to the manufacturer, yields 15-60 ng/µl of DNA. DNA from UNC breast cancer patient samples were obtained from lymphoblastoid cell lines as described previously (39). Paraffin-embedded tissue (PET) samples from breast cancer patients were used for DNA isolation in the event there was insufficient DNA isolated from the blood samples.…”
Section: Genotype Analysismentioning
confidence: 99%
“…Nevertheless, the involvement of these two genes in DNA DSB repair provides some clue to the etiology of the remaining 95% of breast cancers. Ionizing radiation and other endogenous factors can cause DSBs [15,16] that could increase risk for breast cancer [9][10][11]17]. If any impairment exists in the H2AFX gene, it is possible that DSBs could not be repaired correctly or efficiently, leading to chromosomal breaks and genomic instability and thus predisposition to cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the conflicting results in the literature may be related to: (1) study sample size and related statistical power, (2) PHA-induced PBLs vs lymphoblastoid cell lines, and (3) parameters used for interpreting the study results. 5,9,15,16 Another interesting finding in this study is that response of PBLs to PHA is lower in breast cancer cases compared to that in controls. Several earlier studies reported that PBLs from cancer patients are less responsive to mitogenic stimulation by PHA and other plant lectins compared to healthy controls.…”
Section: Discussionmentioning
confidence: 53%
“…12,15,16,23 Mutations in BRCA1 or ATM are risk factors for breast and ovarian cancers. 2,24 The results from recent studies suggest that BRCA1 plays critical roles in Cell cycle delay in breast cancer risk and radiosensitivity Dovepress submit your manuscript | www.dovepress.com Dovepress DNA repair, recombination, checkpoint control of the cell cycle, transcription, and S-and G 2 -phase checkpoints in response to IR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation